Pengolahan Bahan Pustaka yang Terintegrasi Radio Frequency Identification (RFID) di Perpustakaan Universitas Hasanuddin - Marwansyah H, Andi; Iskandar,; Sulaiman, Umar (Literatify : Trends in Library Developments, 2025)
The Hasanuddin University Library manages more than 516,000 collections, which poses challenges in efficiency and accuracy with conventional barcode systems. To address these issues, this research offers a solution based on Radio-Frequency Identification (RFID) as a more modern, adaptive, and accurate technology. The objective of this research is to examine the processing of library materials integrated with RFID at the Hasanuddin University Library in Makassar. This study employed a descriptive qualitative design. Data were collected through interviews, observations, and documentation. Data were analyzed using the Miles and Huberman interactive model, including data collection, reduction, display, and conclusion drawing. Validity was ensured through source and method triangulation. Findings reveal that RFID integration covers stamping, digital inventory, classification, bibliographic input, labeling, RFID tagging, circulation testing, and shelving. The integration of RFID with Inlislite automation significantly improved efficiency, accuracy, and security, while supporting the development of smart libraries in higher education institutions.